Experimental determination of the effective indenter shape and ε-factor for nanoindentation by continuously measuring the unloading stiffness - Merle, Benoit; Maier, Verena; Göken, Mathias; Durst, Karsten (Journal of Materials Research, 2012)
The Oliver and Pharr method for evaluating nanoindentation load–displacement data is based on the measurement of the contact stiffness, which is usually determined at the very beginning of the unloading sequence, or, using dynamic nanoindentation, continuously during the whole loading segment. A new experimental method has been developed to continuously monitor the contact stiffness throughout the unloading sequence. It provides supplementary information about the shape and area of the residual impression, as well as a direct measurement of the shape of the effective indenter previously introduced by Pharr and Bolshakov. The new method was applied to indentations on fused silica, sapphire, nanocrystalline nickel, and ultrafine-grained aluminum. Lastly, the new procedure was adapted to directly measure the epsilon factor used in the Oliver and Pharr method. A value of 0.76 was found from indentation into fused silica, in close agreement with literature values.
EAM Import::2019-03-14